Bio-accessibility of bioactive compounds (ACE inhibitors and antioxidants) from extruded maize products added with a red seaweed Porphyra columbina - Cian, Raúl Esteban (2014)
An expanded maize product added with red seaweeds Porphyra columbina (3.5g100g-1) was developed and bio-accessibility of minerals and bioactive compounds such as ACE inhibitors and antioxidants provide by algae were evaluated using a pepsin/pancreatin digestion and equilibrium dialysis method. Extruded maize added with red seaweed showed higher dialyzability of ACE inhibitor compounds (41.0% ACE inhibition), total phenolic content (0.83mg gallic acid/g dialysate) and antioxidant capacity (36.6% DPPH inhibition, 2.4mM TEAC, power reduction and 99.4% copper-chelating activity) than extruded maize. Results about bio-accessibility of bioactive compounds provided by red edible seaweeds may help food technologists to tailor new bio-functional foods, such as functional snacks.